Chromosome 8p tumor suppressor genes SH2D4A and SORBS3 cooperate to inhibit interleukin-6 signaling in hepatocellular carcinoma - Plöger, Carolin; Waldburger, Nina; Fraas, Angelika; Goeppert, Benjamin; Pusch, Stefan; Breuhahn, Kai; Schirmacher, Peter; Rössler, Stephanie (Hepatology, 2016)
Several chronic inflammatory liver diseases, e.g., chronic hepatitis B or C viral infection and steatohepatitis, have been shown to predispose to the development of hepatocellular carcinoma (HCC). In patients with chronic liver disease, interleukin-6 (IL-6) serum levels are elevated and increase even more when HCC develops. However, the impact and regulatory mechanisms of IL-6 signaling during hepatocarcinogenesis are still poorly defined. Here, we show that gene expression profiles of patients with chromosome 8p loss correlate with increased IL-6 signaling. In addition, the chromosome 8p tumor suppressor genes Src homology 2 domain containing 4A (SH2D4A) and Sorbin and Src homology 3 domain containing 3 (SORBS3) together exerted greater inhibition of cell growth and clonogenicity compared to a single gene. Overexpression of SH2D4A and SORBS3 in HCC cells led to decreased IL-6 target gene expression and reduced signal transducer and activator of transcription 3 (STAT3) signaling. In situ and in vitro coimmunoprecipitation assays revealed that SH2D4A directly interacts with STAT3, thereby retaining STAT3 in the cytoplasm and inhibiting STAT3 transcriptional activity. On the other hand, SORBS3 coactivated estrogen receptor α signaling, leading indirectly to repression of STAT3 signaling. In human HCC tissues, SH2D4A was positively associated with infiltrating regulatory and cytotoxic T-cell populations, suggesting distinct immunophenotypes in HCC subgroups with chromosome 8p loss. Thus, the genetically linked tumor suppressors SH2D4A and SORBS3 functionally cooperate to inhibit STAT3 signaling in HCC. Conclusion: The chromosome 8p tumor suppressor genes SORBS3 and SH2D4A are physically and functionally linked and provide a molecular mechanism of inhibiting STAT3-mediated IL-6 signaling in HCC cells. (Hepatology 2016;64:828-842)